A Policy Model and Framework for Context-Aware Access Control to Information Resources†. (18th July 2018) - Kayes, A S M; Han, Jun; Rahayu, Wenny; Dillon, Tharam; Islam, Md Saiful; Colman, Alan
Abstract: In today's dynamic ICT environments, the ability to control users' access to information resources and services has become ever important. On the one hand, it should provide flexibility to adapt to the users' changing needs, while on the other hand, it should not be compromised. The user is often faced with different contexts and environments that may change the user's information needs. To allow for this, it is essential to incorporate the dynamically changing context information into the access control policies to reflect different contexts and environments through the use of a new context-aware access control (CAAC) approach with both dynamic associations of user-role and role-permission capabilities. Our proposed CAAC framework differs from the existing access control frameworks in that it supports context-sensitive access control to information resources and dynamically re-evaluates the access control decisions when there are dynamic changes to the context. It uses the dynamic context information to specify the user-role and role-permission assignment policies. We first present a formal policy model for our framework, specifying CAAC policies. Using this model, we then introduce a policy ontology for modeling CAAC policies and a policy enforcement architecture which supports access to resources according to the dynamically changing context information. In addition, we demonstrate the feasibility of our framework by considering (i) the completeness, correctness and consistency of the ontology concepts through application to healthcare scenarios and (ii) the performance and usability testing of the framework when using desktop and mobile-based prototypes.